Kardiomiopati Peripartum sebagai Penyebab Stroke pada Usia Muda - Leon Abirawa; Viky Victory; Muhammad Firdaus Kamil (PT Kalbe Farma Tbk., 2024)
Peripartum cardiomyopathy can be a cause of stroke in the younger population. A case of stroke in a young woman caused by peripartum cardiomyopathy with early presentation mimics pulmonary tuberculosis is presented. This is a cause for concern in countries with a high prevalence of TB infection.